2021
DOI: 10.1080/00224065.2021.1903822
|View full text |Cite
|
Sign up to set email alerts
|

Deep multistage multi-task learning for quality prediction of multistage manufacturing systems

Abstract: In multistage manufacturing systems, modeling multiple quality indices based on the process sensing variables is important. However, the classic modeling technique predicts each quality variable one at a time, which fails to consider the correlation within or between stages. We propose a deep multistage multi-task learning framework to jointly predict all output sensing variables in a unified end-to-end learning framework according to the sequential system architecture in the MMS. Our numerical studies and rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 49 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…, 2020; Jin et al. , 2021; Yan et al. , 2021), it is no surprise that big data analytics in manufacturing is a popular topic.…”
Section: Science Mapping Of DL Applications In Manufacturing Operatio...mentioning
confidence: 99%
See 1 more Smart Citation
“…, 2020; Jin et al. , 2021; Yan et al. , 2021), it is no surprise that big data analytics in manufacturing is a popular topic.…”
Section: Science Mapping Of DL Applications In Manufacturing Operatio...mentioning
confidence: 99%
“…These data points may be of different kinds, originating from diverse functional metrics as they go from one functional process to a more sophisticated one (Weng et al, 2019;Fang et al, 2020;Lian et al, 2021). With so much data available (Jang and Nemeh, 2017;Jiang et al, 2020;Jin et al, 2021;Yan et al, 2021), it is no surprise that big data analytics in manufacturing is a popular topic.…”
Section: Knowledge Clusters (Themes) Via Keyword Coupling Analysis (Ro1)mentioning
confidence: 99%
“…Zhao et al (2014) performed process optimization for grinding and polishing process parameters to improve the surface quality and decrease the surface roughness of products. Yan et al (2021) proposed a deep multistage multi-task model that considers different response variables at the same time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the DL model having higher computational time and complexity than the machine learning approach, DL provides robust results, particularly in the big dataset. Several studies also reported that DL can be used to build a high-performance prediction model in many areas such as agriculture [13], manufacturing [14], and even behavioral science [15].…”
Section: Introductionmentioning
confidence: 99%